DIGITAL HEALTH FOR IMPROVING MANAGEMENT OF ACUTE CORONARY SYNDROME - Vasić, Ana (Medicinski podmladak, 2023)
In the management of acute coronary syndrome (ACS), providing the best and most equitable care to all patients is a major challenge. Clinical studies pinpoint the areas of pre-hospital and hospital care that need improvement. In Serbia, problems relate to timely ACS symptoms recognition, time to first medical contact, diagnostic accuracy, rehabilitation. A novel strategy called "Digital Health" (DH) can aid in resolving these issues. In this mini-review several digital health interventions are suggested as ways to improve ACS patient care.